THE ROLE OF THE INTERNET IN COMMUNICATIVE LANGUAGE LEARNING - Mansurova, Shohista (Журнал иностранных языков и лингвистики, 2023)
In our article, when implementing a communicative approach on the Internet, user-friendliness and communicative approaches will be considered. A communicative approach is a communication modeling strategy that aims to create a psychological and linguistic willingness to communicate, a conscious understanding of the material and how to deal with it, and an understanding of the prerequisites for the effectiveness of the statement.